Brain expansion in early hominins predicts carnivore extinctions in East Africa - Faurby, Søren (Ecol Lett, 2020)
While the anthropogenic impact on ecosystems today is evident, it remains unclear if the detrimental effect of hominins on co‐occurring biodiversity is a recent phenomenon or has also been the pattern for earlier hominin species. We test this using the East African carnivore fossil record. We analyse the diversity of carnivores over the last four million years and investigate whether any decline is related to an increase in hominin cognitive capacity, vegetation changes or climatic changes. We find that extinction rates in large carnivores correlate with increased hominin brain size and with vegetation changes, but not with precipitation or temperature changes. While temporal analyses cannot distinguish between the effects of vegetation changes and hominins, we show through spatial analyses of contemporary carnivores in Africa that only hominin causation is plausible. Our results suggest that substantial anthropogenic influence on biodiversity started millions of years earlier than currently assumed.